Esophagectomy without thoracotomy in grade IV megaesophagus - Santandreu, Jorge; Vázquez, Aníbal; Perrone, Luis; Delgado, Bolívar (Cirugía del Uruguay, 1993)
The authors present a patient with grade IV megaesophagus, studied by means of radiology and endoscopy and tested tor Chagasic etiology. An elective tactic of esophagectomy without thoracotomy was performed with good postoperative evolution.